Analisis Kemampuan Awal Multi Level Representasi Mahasiswa Tingkat I pada Konsep Reaksi Redoks - Indah Langitasari (Universitas Sultan Ageng Tirtayasa, 2016)
Abstract: Analysis of students' initial ability before teaching the chemistry concept are very important to determine the correct techniques in learning concept. The objectives of this study was to identify the first year students' initial ability to describe and explain redox reactions concept using macroscopic, submicroscopic and symbolic representation. This study applies pre-experimental research design involving a group of subjects. The diagnostic instrument consists of 15 items two-tier multiple choice and 2 items essay. Data were analyzed descriptively by tabulating students' answers of each question. The results showed that the first year students' initial understanding to the redox reactions concept was very low. Students have not been able to describe and explain the observed redox reactions (macroscopic) in terms of the atoms, molecules and ions that were involved in the reactions. This results also indicated the first year students' symbolic and microscopic understanding very limited and only 2.9 % of students were able to make the connection between macroscopic observations, symbolic and submicroscopic representation . Keywords:  Initial ability, Redox reaction, Multiple levels of representation Abstrak: Analisis tingkat pemahaman awal mahasiswa sebelum mengajarkan konsep kimia sangat penting agar dapat menentukan teknik yang tepat dalam pembelajaran konsep.  Penelitian ini bertujuan untuk menguji kemampuan awal mahasiswa tingkat I dalam mendeskripsikan dan menjelaskan konsep reaksi redoks menggunakan representasi makroskopik, submikroskopik dan simbolik. Penelitian ini menggunakan desain penelitian pra-eksperimental dengan melibatkan satu kelompok subjek. Instrumen tes terdiri dari 15 soal two tier dan 2 soal essay. Data hasil penelitian dianalisis secara deskriptif dengan mentabulasikan jawaban mahasiswa untuk masing-masing item soal. Hasil penelitian menunjukkan bahwa pemahaman awal mahasiswa tingkat I terhadap konsep reaksi redoks masih tergolong sangat rendah. Mahasiswa belum mampu mendeskripsikan dan menjelaskan hasil pengamatan reaksi redoks (makroskopik) dalam bentuk atom, molekul, dan ion yang terlibat dalam reaksi. Hal ini mengindikasikan bahwa pemahaman simbolik dan submikroskopik mahasiswa tingkat I masih sangat terbatas dan hanya 2,9% mahasiswa yang mampu membuat hubungan antara pengamatan makroskopik, representasi simbolik dan gambaran submikroskopik. Kata kunci:  Kemampuan awal, Reaksi redoks, Multi level representasi